Regulation and production of contemporary literature: An examination of literary evolution in the digital age - Adawiyah, Robiatul (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2024)
The evolution of technology has significantly influenced the realm of literature. Once predominantly disseminated through oral and print mediums, literary works are now increasingly emerging in digital formats. The emergence of digital literature phenomena has impacted literary works' processes, outcomes, and production. Digital literature is not merely termed 'digital' due to its medium; it also entails form and regulatory framework differences. Unlike conventional literary works published in print, the production of digital literature is characterized by swiftness and demands rapidity. Employing netnography methodology with a descriptive approach to social change, this article explores the regulation of digital literature production, innovations in digital literary forms, the process of producing digital literature, and the changes occurring in print literature. The analytical process involves observing several platforms publishing digital literature, examining printed literary products, collecting regulatory data from various digital literary platforms, presenting the data, and drawing conclusions. The findings reveal that each digital literary platform has distinct regulations, unlike major print publishers with nearly uniform regulations. Furthermore, the rapid development of digital literature indirectly compels print literature to showcase greater creativity in marketing efforts to withstand the onslaught of innovative digital literary products in the contemporary era.